Praktična prilagodba klasičnih uređaja za ubrizgavanje goriva u motorima velike snage za teretna vozila - Anton Černaj; Želimir Dobovišek; Breda Kegl (Promet - Traffic&Transportation, 1970)
Basic requirements related to fuel injection system of upgradedturbocharged articulated truck diesel engines are listedand discussed. An example of the FIE matching approach toupgrading of a heavy duty diesel engine is presented. The applicationof hollow cam fuel injection pump may offer a furtherextension of its use in order to uprate diesel engine peiformance.